High Current Pulse Transducer for Metal-Oxide Surge Arresters - Gurevich, V. (Електротехніка і електромеханіка, 2007)
High-voltage arresters of 160 kV and higher voltage types based on zinc-oxide varistors are important and expensive devices. The main imperfection of existing devices for the varistors monitoring is necessity of human intervention to work with them. A simple automatic high-current pulse transducer included in SCADA system by means of a radio transmitting- receiving set and intended for the arresters control is introduced.